Transforming Agriculture under Viksit Bharat 2047: Pathways to a Sustainable and Prosperous Agricultural Future - Dr V. Murugesh; Dr. P. Govindaraj (The Bioscan, 2026)
India's agricultural sector stands at a critical inflection point as the nation charts its course toward the Viksit Bharat 2047 vision an ambitious agenda to transform India into a fully developed nation by the centenary of its independence. Agriculture, which employs approximately 42% of the workforce and contributes nearly 18% to the gross domestic product (GDP), is central to this vision. However, persistent structural challenges including smallholder fragmentation, water scarcity, climate vulnerability, post- harvest losses, and inadequate market linkages continue to impede progress. This article examines the multidimensional transformation of Indian agriculture within the Viksit Bharat framework, analyzing key policy interventions, technological innovations, institutional reforms, and sustainability strategies. Drawing on secondary data, policy documents, and scholarly literature, the study identifies critical levers for agricultural modernization, including digital agriculture, precision farming, agri-value chain development, and climate-smart practices. The findings suggest that achieving the agricultural goals of Viksit Bharat 2047 requires an integrated approach that harmonizes technological advancement with social equity, environmental sustainability, and institutional capacity building.